Age-Dependent Risk of Graft Failure in Young Kidney Transplant Recipients. Issue 6 (June 2017) - Kaboré, Rémi; Couchoud, Cécile; Macher, Marie-Alice; Salomon, Rémi; Ranchin, Bruno; Lahoche, Annie; Roussey-Kesler, Gwenaelle; Garaix, Florentine; Decramer, Stéphane; Pietrement, Christine; Lassalle, Mathilde; Baudouin, Véronique; et al.
Abstract : Background: The risk of graft failure in young kidney transplant recipients has been found to increase during adolescence and early adulthood. However, this question has not been addressed outside the United States so far. Our objective was to investigate whether the hazard of graft failure also increases during this age period in France irrespective of age at transplantation. Methods: Data of all first kidney transplantation performed before 30 years of age between 1993 and 2012 were extracted from the French kidney transplant database. The hazard of graft failure was estimated at each current age using a 2-stage modelling approach that accounted for both age at transplantation and time since transplantation. Hazard ratios comparing the risk of graft failure during adolescence or early adulthood to other periods were estimated from time-dependent Cox models. Results: A total of 5983 renal transplant recipients were included. The risk of graft failure was found to increase around the age of 13 years until the age of 21 years, and decrease thereafter. Results from the Cox model indicated that the hazard of graft failure during the age period 13 to 23 years was almost twice as high as than during the age period 0 to 12 years, and 25% higher than after 23 years. Conclusions: Among first kidney transplant recipients younger than 30 years in France, those currently in adolescence or early adulthood have the highest risk of graft failure. Abstract : This retrospective national French cohort study confirms previous findings that the risk of graft failure is increased between 13 and 21 years of age compared to younger or older kidney transplant population. Unfortunately, the reasons behind this observation are not known.